The Psychometric Properties of the Farsi Version of the Hooper Sexual Problems Questionnaire - Mahshid Sasanpour; Amir Azizi (Journal of Holistic Nursing and Midwifery)
Introduction: Despite the desirable characteristics of the Hooper Sexual Problems questionnaire in studying the problems and strengthening sexual relations, the standardization of the questionnaire has not been done in Iran. Objective: The current study aimed at standardizing the Hopper sex problems questionnaire in Iranian couples. Materials and Methods: The current methodological study was conducted on 310 couples (620 people), selected by multistage random sampling method, to assess the construct validity (convergent and differential validity), criterion validity, and the internal consensus estimation of the questionnaire. In the next stage, 120 couples (240 people) were selected through convenience sampling method to estimate the structural validity, temporal stability, and reliability of the observers. The formal validity and qualitative content validity, structural validity (exploratory factor analysis), and criterion validity were used to estimate the validity of the questionnaire. The Cronbach alpha was used in order to measure the internal consistency of the questionnaire. The test-retest was used to check the temporal stability of the questionnaire. Finally, the Kappa coefficient was used to assess the reliability of the observers. Results: The results of qualitatively checking the validity was satisfactory. The convergent validity was satisfactory with marital satisfaction questionnaire (r=0.80) and sexual satisfaction questionnaire (r=0.74) and differential doping with mental health questionnaire (r=-0.39). The criterion validity of the sexual problem questionnaire determined 37.8% and 62.1% of the marital satisfaction and sexual satisfaction variances, respectively. Exploratory factor analysis showed that the questionnaire items explained at least 55% and at most 92% of the total variance of the test. The Cronbach alpha of the questionnaire was 0.976, the reliability of the retest was 0.63, and the mean agreement coefficient between the experts was 0.64 (P<0.05). Conclusion: The Hooper Sexual Problems questionnaire has desirable reliability and validity and can be used as a tool to study and evaluate sexual relations.